1998
DOI: 10.1029/98jd02399
|View full text |Cite
|
Sign up to set email alerts
|

Natural microseepage of methane to the atmosphere from the Denver‐Julesburg basin, Colorado

Abstract: Abstract. Methane fluxes were measured at locations across the Denver-Julesburg (DJ) basin of northeastern Colorado, which is in a semiarid climate. There is a potential for microseepage of thermogenically derived methane and light hydrocarbons to the atmosphere, which during drier or colder seasons may exceed the capacity for methanotrophic oxidation in the shallow soils. Triplicate measurements of methane flux in three seasons across the basin found areas of positive and negative fluxes in a patchy pattern w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
(25 reference statements)
1
18
0
1
Order By: Relevance
“…The increased range and standard deviation in the winter were also consistent with the background data of Klusman et al 21,24 Cumulative frequency plots suggested that in each season there were a high-flux and a low-flux population.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…The increased range and standard deviation in the winter were also consistent with the background data of Klusman et al 21,24 Cumulative frequency plots suggested that in each season there were a high-flux and a low-flux population.…”
Section: Resultssupporting
confidence: 75%
“…10,16 Due to the reliance of methanotrophs on diffusion from both the atmosphere and the subsurface, the habitat of these microbes can be expected to be in a relatively narrow band in the shallow interval of the landfill cover. This is also consistent with lower winter rates of methanotrophic oxidation found in native soils with grass/shrub cover, and in a semiarid climate found by Klusman et al [20][21][22][23][24] EXPERIMENTAL METHODS Static flux chamber methods were utilized in this study to evaluate seasonal CH 4 fluxes over the Rooney Road landfill in Jefferson County, CO. The landfill had received MSW with a high proportion of CH 4 -prone materials such as paper and food wastes.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…On the other hand, they also represent potential sources of greenhouse gas emissions to the atmosphere. Large emissions of CH 4 from hydrocarbon prolific basins to the atmosphere were already detected in several places (Klusman and Jakel, 1998;Etiope, 2004;Etiope et al, 2008;Etiope and Klusman, 2010). Methane emissions from hydrocarbon reservoirs and source rocks may also affect the potential of soils as carbon sink and the groundwater chemistry.…”
Section: Implications For Natural Gas Potential and Greenhouse Gas Emmentioning
confidence: 98%